Association between Meeting the Physical Activity Guidelines and Participation in 'Sports for All' and the Risk of Hypertension in Community-dwelling Korean Adults - Deogjo Jung; Keun-Ok An; Junghoon Kim (Asian Society of Kinesiology, 2018)
OBJECTIVES We aimed to evaluate physical activity patterns according to participation in the 'sports for all' programs in community-dwelling Korean adults. We also investigated the association between meeting physical activity guidelines and participation in sports activities and the risk of hypertension. METHODS For the present study, we clustered and randomly selected participants from Chungcheongbuk-do in Korea. From a total of 520 participants, 493 completed the survey, and the response rate was 92%. After excluding participants who had missing data for physical activity, demographics, health-related behaviors, and clinical health conditions, a total of 481 participants were included in the study. RESULTS We observed a lower risk of hypertension in the sports activities group than in the inactive group after adjustment for age and sex (OR: 0.42, 95% CI: 0.17-0.99). The results were unchanged after adjustment for education levels and household income. In the fully adjusted model, the ORs for hypertension were 0.36 (95% CI: 0.13-0.97) for the sports activity group and 0.33 (95% CI: 0.14-0.78) for those who met the physical activity guidelines. CONCLUSIONS The criterion of meeting the physical activity guidelines was significantly associated with a decreased risk of hypertension. In addition, participation in the sports for all program without meeting the recommended level of physical activity was independently associated with a lower risk of hypertension.